Potentials of Palm Oil as New Feedstock Oil for a Global Alternative Fuel: A review - Mohd Hafizil, Mat Yasin; R., Mamat; G., Najafi; Ali, Obed Majeed; Ahmad Fitri, Yusop; Mohd Hafiz, Ali (Elsevier, 2017)
Increasing in oil consumption and ridiculous prices has caused the urgency for the main global oil industry players to search new alternative fuels which is biofuels. Biodiesel is better option to replace the crude oil due to its similar characteristics and sustainable. This paper will review the biodiesel produced and implementation from palm oil in Malaysia and current engine research that related to palm oil. Precedency given to the palm oil as it is main raw stock for biodiesel produced in Malaysia. Among scopes of this paper are to discuss current issues related to the palm biodiesel production and specific use in diesel engines. Another issue that arisen for Malaysia is to promote the palm oil as the alternative fuel that meets the stringent regulations and standards in Europe and North America. This paper also briefly covers the continuous global biodiesel consumption trend including the constraints that faced by Malaysia for leading the global biodiesel market with the benefits and drawbacks of palm oil biodiesel as an alternate fuel compared to the other common biodiesel sources.